Synthesize and characterization of putrescine containing sulphur - Sahabudin, Adzly H; Fong, Fiona H; Abdul Ghani, Radiah (Bahagian Hal Ehwal Akademik, Universiti Teknologi MARA Cawangan Pulau Pinang, 2016)
Compounds containing sulphur such as organosulphur compounds are well known for their anticancer properties. Addition of sulphur in polyamine is expected to improve the specificity due to the transport to the targeted cells efficiently via polyamine transport system added with the anticancer properties possess by the sulphur donor atom. Putrescine with a polyamine moiety acted as cell delivery vector was synthesized to incorporate sulphur into the structure. The synthesized product was later characterized using various physicochemical techniques for structural determination.